Marine and Freshwater Plants: Challenges and Expectations - Maréchal, Eric (Frontiers in Plant Science, 2019)
The past decades have seen an increasing interest on the biology of photosynthetic species living in aquatic environments, including diverse organisms collectively called “algae.” If we consider the relative size of scientific communities, marine and freshwater plants have been overall less studied than terrestrial ones. The efforts put on land plants were motivated by agriculture and forestry, applications for human industry, easy access to terrestrial ecosystems, and convenient cultivation methods in fields or growth chambers. By contrast, the fragmentary knowledge on the biology of algae, the hope to find in this biodiversity inspiration for biotechnologies, and the emergency created by the environmental crisis affecting oceans, lakes, rivers, or melting glaciers, have stressed the importance to make up for lost time. Needed efforts embrace a broad spectrum of disciplines, from environmental and evolutionary sciences, to molecular and cell biology. In this multiscale view, functional genomics and ecophysiology occupy a pivotal position linking molecular and cellular analyses and ecosystem-level studies. Without pretending to be exhaustive and with few selected references, six grand challenges, requiring multidisciplinary approaches, are introduced below.